Cuidado e formação em Heidegger: bases filosóficas para uma ressignificação da Bildung - Doro, Marcelo José (2019)
This study presents the results of a research on the topic of education, which reference is the philosophy of Martin Heidegger. The guiding question of the research is whether it is possible to identify, in the writings of the first phase of this philosopher’s thought, elements for a current answer to the problem of education. What we call the “problem of education” is the possibility of individuals to cultivate and guide themselves from and in their world. Our interpretative hypothesis is that, even without explicitly appearing as such, the topic of education remains on the horizon of Heidegger’s discussions about the human condition. The investigation of this hypothesis originates the general objective of the study: to identify aspects and concepts of the first phase of Heidegger’s thought that are relevant to the discussion and update on the concept of education. A complementary hypothesis indicates the semantic richness of the concept of care and its constitutive moments as the basis for the ontological movement that leads from an initial condition of non-formation to an authentic self-education. The characterization of this concept and its exploitation in relation to the topic of education constitute the specific objectives of the research. Additionally, as such hypotheses are confirmed, revealing Heidegger's response to the problem of education, this study shows how such response stands in relation to the classical idea of Bildung and its Greek origin, paideia. The nature of the problem and the objectives set for its confrontation reveal beforehand the bibliographical character of the research, which is guided by two fundamental hermeneutical principles: first, the need to maintain interpretative coherence between the whole and the parts, aiming to understand the parts from the whole and vice versa; and second, the respect for the historicity of ideas. As Being and Time is the main work of the first phase of Heidegger’s thought, it becomes the basic reference of this study. Other writings of this period are also consulted, especially the courses of Introduction to Philosophy and The Basic Problems of Phenomenology, as well the text of Plato’s Doctrine of Truth. The central thesis presented based on the research performed is that Heidegger’s philosophy offers a response to the problem of education, which, in general terms, remains close to tradition, but is substantially different. Education is equivalent to transformation, by individuals, from their initial condition of unreflective immersion in the world, to be conducted free of absolute truths or universal ideals; education from the perspective of Heidegger’s philosophy is constituted by the awakening of individuals to their radical freedom, which occurs in a constant struggle against worldly tendencies to concealment and dissimulation of their being (and power-being) in the world. From this redefined idea of education, it may be possible not only to support a critique on the limits of the strictly professional training that permeates the current discussions and educational practices, but also to outline the general guidelines for an education that respects and favors the ontological freedom of individuals.